The mobility and dissemination of blaOXA-48 and blaNDM carbapenemase genes within clinical Escherichia coli isolates - Ridley, Zack (2025)
The spread of antimicrobial resistance within the global population is a matter of serious concern with extensive impacts, but there is a particular severity to disproportionately of resistance spread within hospital settings. These settings act as hotspots and epicentres for the generation and dissemination of a sleugh of antibiotic-resistant bacteria. The environment of high antibiotic use, high concentration of infected individuals or immunocompromised individuals and the frequency of exposure to external bacteria through catheters and IVs etc, provides the ideal environment for the development of multidrug resistant bacterial isolates with unprecedented resistance to commonly applied clinical antibiotics and mechanisms of gene mobility. A particular concern is the rise of resistance towards the carbapenem class of antibiotics which are considered antibiotics of last resort, only used in the most severe of infections. As the strength of resistances increase however, so does the use of these carbapenems, which has resulted in a steep increase in the cases of carbapenem resistant bacteria being observed. The production of the prolific NDM and OXA-48-like enzymes in bacteria has conferred concerning resistance to carbapenems and the genes that encode for them are frequently observed on plasmids bearing the ability to transfer themselves between bacteria of the same and different species and plasmids containing mobile genetic elements that can transfer them into more mobile plasmids. The goal of this research is to examine the varieties of these carbapenem resistance genes in E. coli isolates collected from patients in a hospital setting and to identify the subtypes of NDM and OXA-48 that dominate in the bacterial population within the hospital, and which features of the plasmids are shared through them to form an idea of the phylogeny. This snapshot of data from a clinical setting can then be used as an insight into the state of carbapenem resistance in the UK as a whole.